Tata Kelola Kolaboratif dalam Upaya Percepatan Penurunan Stunting di Kabupaten Buol - Syamsiar I Mahmud; Nurwinda Nurwinda (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2026)
Efforts to reduce stunting in Buol Regency depend not only on the existence of health programs, but also on how well institutions work together and how communities respond to the interventions. Earlier studies have generally focused on policy implementation, intersectoral cooperation, and the Penta Helix approach, while studies on collaborative governance in socio-cultural contexts and 3T areas remain limited. This research examines how collaborative governance supports the acceleration of stunting reduction in Buol Regency using Ansell and Gash’s framework, which includes face-to-face dialogue, trust building, commitment, shared understanding, and intermediate outcomes. This research used a qualitative approach with a case study method. The data were obtained from interviews, field observation, and relevant documents, and were then examined using the interactive analysis model developed by Miles, Huberman, and Saldaña. The findings show that cross-sectoral coordination has been implemented, but it is still constrained by low acceptance of nutritious food innovations, reliance on traditional medicine, concerns about immunization, and uneven community participation. This study emphasizes the need for collaborative governance that strengthens trust, participatory dialogue, and culturally adaptive program approaches.